Romanian Fiscal Policies: Do They Fight or Exacerbate the Crisis? - Nutu, A. O.; Ionita, S. (2012)
As the financial crisis deepens in Romania, public expectations from the budget and the Government's measures package remain high, but options remain limited. While some of the fiscal instruments proposed worldwide could arguably have benefic impacts on the Romanian economy if they could only be properly implemented, our budgetary sector is now constrained to adopt austerity measures. The fiscal policy needs time to regain credibility after years of incoherence, and commitments made in the elections year 2008 prove to be extremely costly today.